2018
DOI: 10.1007/s00122-018-3253-9
|View full text |Cite
|
Sign up to set email alerts
|

Exploring and exploiting the genetic variation of Fusarium head blight resistance for genomic-assisted breeding in the elite durum wheat gene pool

Abstract: Key message Genomic selection had a higher selection response for FHB resistance than phenotypic selection, while association mapping identified major QTL on chromosome 3B unaffected by plant height and flowering date. Abstract Fusarium head blight (FHB) is one of the most destructive diseases of durum wheat. Hence, minimizing losses in yield, quality and avoiding contamination with mycotoxins are of pivotal importance, as durum wheat is mostly used for human consumption. While growing resistant varieties is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
77
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(84 citation statements)
references
References 106 publications
7
77
0
Order By: Relevance
“…Multivariate GS uses secondary traits that are genetically correlated with a trait of interest as covariates in a GS model, which can increase prediction accuracy, especially when the trait of interest has a low heritability and the covariate trait has a high heritability (Calus & Veerkamp, 2011; Guo et al., 2014; Jia & Jannink, 2012). Multiple studies have evaluated the use of MVGS for FHB resistance in wheat; however they have primarily focused on SEV as a trait of interest and only used HD and PH as covariates (Moreno‐Amores et al., 2020; Schulthess et al., 2018; Steiner et al., 2019). An MVGS model was also used to predict DON using an INC, SEV, and FDK index (Rutkoski et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Multivariate GS uses secondary traits that are genetically correlated with a trait of interest as covariates in a GS model, which can increase prediction accuracy, especially when the trait of interest has a low heritability and the covariate trait has a high heritability (Calus & Veerkamp, 2011; Guo et al., 2014; Jia & Jannink, 2012). Multiple studies have evaluated the use of MVGS for FHB resistance in wheat; however they have primarily focused on SEV as a trait of interest and only used HD and PH as covariates (Moreno‐Amores et al., 2020; Schulthess et al., 2018; Steiner et al., 2019). An MVGS model was also used to predict DON using an INC, SEV, and FDK index (Rutkoski et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that the incorporation of the G×E effect and multiple traits in the GS model increased the prediction accuracy by 9.6% for low-heritability traits across environments (Ward et al, 2019b). Notably, the higher prediction ability of the phenotypic selection over GS with higher selection response vice versa documented by Steiner et al (2019) underscores that genomics and phenomics should be complementary to further cultivar improvements. Similarly, the higher accuracy of genome-wide maker-based models tested in recent studies to detect even minor effect QTL unchecked by MAS ensures the success of GS for future rusts resistance in SRWW (Todorovska et al, 2009;Bulli et al, 2016;Steiner et al, 2017).…”
Section: Challenges and Breeding Strategies For Fhb Lr And Sr Resismentioning
confidence: 99%
“…Interestingly, the smallest average number of Fusarium colonies was observed on the glumes and grain of durum wheat. There are many findings concerning the paucity of FHB resistance in durum wheats [39][40][41]. Thus, a low level of Fusarium infections on durum wheat grain and glumes may be an indicator of the potential resistance genes presence which might be useful in durum wheat breeding, however that should be investigated in more detail.…”
Section: Discussionmentioning
confidence: 99%